إساءة الفهم في تأسيس علم العروض، موقف الخليل من مصطلحات عروض ما قبل الإسلام أنموذجا - Shakir Jumaah, Lect. Dr. Mohammed (Basra studies journal, 2025)
To examine the Arab prosody according to Harold Bloom’s perspective on the deconstructive approach, which views the foundation of science as based on a deliberate misunderstanding of the past in order to produce new theories and transcend old ones. Curriculum: the researcher followed the analytical approach in studying a set of terms used by Al-Khalil bin Ahmed Al-Farahidi, and it have shown that Al-Khalil changed the concepts of some terms of presentation in order to conform to his view towards the prosody , and used new terms based on his vision of Arab prosody. The research included two requirements. Problems: the researcher face some difficulties related to research, including the lack of books of Al-Khalil bin Ahmed Al-Farahidi, and what one can get is nothing more than opinions scattered in the books quoted by scholars, and the researcher have collected all these opinions and studied them according to the perspective of misunderstanding. Results: Al_ Khalil has changed the terminology that contradicts his prosodic point of view, and this point of view starts from the era of Islam, to impose on the pre-Islamic era a modern point of view, that is, Al_ Khalil established the science of prosody in a contemporary way for his time, and imposed on previous eras to include his concept. Recommendations: I recommend a thorough study of prosody according to this approach, which can deepen the view based on deliberate misunderstanding through which only scientists can establish new sciences.